The impact of financial attitudes and revenue on financial planning through financial behavior - Parulian Parulian; Nataliana Bebasari (Institute of Computer Science (IOCS), 2023)
The study aims to test the impact of financial attitudes and income on financial planning through financial behavior with the object of research of employees of the PT YMMA production department. This type of research is quantitative research with data processed from primary and secondary data obtained from the results of the dissemination of questionnaires with purposive data sampling techniques by disseminating questionnaire online ie google form. The population in the study was 1500 employees and a sample of 100 respondents was obtained. The data analysis method in this study uses software SmartPLS (Partial Least Square) version 3.0. The results of this study show that the variable of financial attitude has no influence on financial planning. Income and financial behavior have a positive and significant impact on financial planning. Financial behavior as an intervening variable is not able to mediate the financial attitude towards financial planning, but financial behaviour is capable of mediating the impact of income on financial planning. Implications to this research can help strengthen the role of financial behavior in financial decision-making. This can help provide a foundation for developing strategies to improve the financial behavior of individuals and families in better planning their finances.